Third ventricle colloid cysts endoscopic approach - Massa, Daniela; Beltrame, Sofía; Rasmussen, Jorge; Kornfeld, Sebastián; Yampolsky, Claudio; Ajler, Pablo (Revista del Hospital Italiano de Buenos Aires, 2017)
Colloid cysts are benign, slow-growing tumors, comprising less than 1% of intracranial tumors. They occur in young adults and are more frequently located on the roof of the third ventricle. The objective of this study is to present a series of patients with Colloid cysts operated endoscopically and analyze advantages and disadvantages of this surgical technique. We performed a retrospective review of Colloid Cysts operated on endoscopically, at the Neurosurgical Department of Hospital Italiano de Buenos Aires in a period of 2 years (2013-2015). Five patients were identified, three women and two men whose average age was 50 years. No perioperative complications were observed, with no recurrences during the follow up period. Conclusion: the endoscopic approach is technically simple and has very low morbidity. Although a complete excision can not always be performed, prospective studies will allow us to define whether if is sufficient to control the disease